(untitled) (Archive of Conferences, 2022)
The content of this article is devoted to highlighting the psychological principles of the differential approach in the psychological analysis of professional activity. Particular attention is paid to such issues as professiogram, analysis of the profession, a differentiated approach to professional activity, psychological aspects of professional activity.